An Analysis on Business Feasibility of Hotel X at Pasuruan Regency, East Java - Leonandri, Dino Gustaf (Jurnal Penelitian Pariwisata, 2020)
This article describes a feasibility study for a hotel development in Pasuruan, East Java. The potential city of Pasuruan has begun to develop as a trade, government and service area and the construction of this hotel is expected to increase local revenue (PAD) as well as both contributing to the economy of the local community and providing benefits to the investors. The research uses qualitative method and data gathered by both interview and data collecting. The variable of this research is business feasibility and the analysis unit is Hotel X. From the research analysis, it was found that development hotel in Pasuruan is feasible and can be continued.